Speech Rate of Children With Developmental Language Disorder in a Narrative Context - Georgiou, Georgios P.; Panteli, Constantina; Theodorou, Elena (My University, 2025)
This study investigates the speech rate of Cypriot Greek-speaking children with developmental language disorder (DLD) as well as the effect of age and gender. The participants were 16 children with DLD ages 4 years 11 months to 8 years 1 month and 22 children with typical language development (TLD) ages 4 years 5 months to 8 years 7 months. Both groups were divided into younger and older groups. All children participated in a storytelling task, and measurements were conducted based on syllables and words per second. The results indicated significant differences between children with DLD and children with TLD in the speech rate, but no differences between younger and older and male and female children of both groups. The stagnancy of speech rate across different age groups demonstrates that children with DLD follow similar developmental trajectories as children with TLD and that speech rate is not affected by gender. Speech rate could be considered as a marker for identifying DLD in Cypriot Greek-speaking children.
Keywords: age; speech rate; developmental language disorder; narrative; Cypriot Greek gender